The Repercussions of the Russian-Ukrainian War on European Security after 2022 - Safih, Mustafa Jafaar; shayal, Azeez Jabur (Dirasat: Human and Social Sciences, 2025)
Objectives: The study aims to present a comprehensive analysis of the impact of the Russian-Ukrainian War on European security after 2022, with a special focus on political, military, and economic repercussions, challenges, and transformations across the European continent. Methods: The study utilizes a descriptive-analytical approach to illustrate and analyze the effects of the Russian-Ukrainian War on European security levels. It also employs a comparative method to assess changes in European security before and after the conflict, by documenting relevant data and statistics related to political, military, and economic changes as a result of the conflict. Results: The study finds that the Russian-Ukrainian War has caused significant tension between Russia and European countries. Political and diplomatic relations have deteriorated, while European nations have responded by enhancing their defense capabilities through increased military spending. Russia has leveraged energy as a tool of political pressure in its foreign policy, impacting European economies through rising energy prices on the one hand, and sanctions imposed on it on the other. Summary: The Russian-Ukrainian war has profoundly affected European security, leading to increased political tensions and fragmentation in the decision-making process within Europe. In response, European countries have focused on boosting military capabilities and armament. Economically, sanctions imposed on Russia have contributed to an aggravated economic crisis and increased inflation rates in Russia.